The understanding of using universal precaution in medical student, ca-assistant and resident in the Faculty of Medicine, Universitas Udayana, Bali-Indonesia - Tham Hong Yuan; I Wayan Niryana; Putu Anda Tusta Adiputra; Made Agus Dwianthara Sueta (DiscoverSys Inc., 2020)
Introduction: This study was reported that among medical students, Co-Assistant (Co-Ass) and resident, several factors such as the academic overload in addition to the students’ non-school activities might contribute to this situation. There is a lack of universal precaution studies among Universitas Udayana students in Bali and in Sanglah Hospital. Thus, the aim of this descriptive study was to examine the understanding of using universal precaution among three categories of students as well as doctors in Universitas Udayana.Method: Study design using a cross sectional model. Data were obtained from 90 current university students and doctors.Result: The highest questionnaire overall scores were obtained was 83 and the lowest scores were 43. The understanding of PPE among medical students, Co-Ass, resident significantly differ in the understanding of PPE (p<0.001). Resident is significantly different (p<0.001) than the other two groups, but there is no significant difference between the Co-Ass and Medical students.Conclusion: This study provides an overall understanding of universal precautions among medical students, Co-Ass and resident in Universitas Udayana. Findings will serve as a basis for future researchers to conduct future intervention studies.